The Potential of Purple Waxy Corn Cob (Zea mays L.) Extract Loaded-Sericin Hydrogel for Anti-Hyperpigmentation, UV Protection and Anti-Aging Properties as Topical Product Applications - Nattawadee Kanpipit; Natsajee Nualkaew; Suthasinee Thapphasaraphong (MDPI AG, 2022)
Sericin-hydrogel formulations incorporating purple waxy corn (Zea mays L.) cob extract (PWCC) were developed as potential topical skin cosmetic products. Sericin has wound healing properties, protects against ultraviolet (UV) radiation, and exhibits anti-inflammatory, anti-oxidation, and anti-tyrosinase activities. PWCC is a rich source of anthocyanins with antioxidants, UV protective, anti-inflammatory, and collagen-enhancing activities. Six hydrogel formulations (S1-S6) were investigated for anti-melanogenesis on the B16F10 melanoma cell line and UV-protection on human keratinocytes (HaCaT) and anti-aging activities on normal human dermal fibroblasts (NHDFs). The results showed that the hydrogel formulations enhanced the anthocyanin permeation through the skin. The S4 formulation indicated the highest inhibition of tyrosinase activity and reduced the melanin pigment, increased the cell viability of the UV-induced HaCaT cells, the inhibition of collagenase and elastase, and increased the collagen type I production without cytotoxicity. Therefore, the PWCC loaded-sericin hydrogels show a high potential as a novel anti-hyperpigmentation, UV protection, and anti-aging products for topical applications.